Performance analysis of a graph coloring algorithm for wavelength assignment in dynamic optical networks - Fonseca, P.; Cancela, L.; Rebola, J. (2022 13th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2022)
In the near future (5 to 10 years), dynamic optical networks will be crucial in global optical communications in order to respond to the fast growing of on-demand services. Routing and wavelength assignment (RWA) planning tools must be developed to effectively deal with the dynamic scenarios requirements. In this work, a simulation tool for RWA in dynamic optical networks was developed and wavelength assignment (WA) was implemented, through a recently proposed graph coloring algorithm, named Small-Buckets algorithm, that allows recolorings to occur. Several fiber based networks have been studied and it has been concluded that the Small-Buckets algorithm originates lower blocking probabilities than the ones obtained with the First fit algorithm. However, to reach this improved performance, the Small-Bucket algorithm requires a larger number of wavelengths and recolorings.